Pengembangan Sistem Informasi Lembar Penilaian Siswa (Studi Kasus: SMA Brawijaya Smart School Malang) - Fara Nur Azizah; Denny Sagita Rusdianto; Komang Candra Brata (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
Assessment is an attempt to find the potential that students have. Assessment is carried out not only from the subject matter, but including from the values ​​of attitudes and skills. These productivity aspects have one person who is responsible and makes a plan for the learning process. SMA Brawijaya Smart School has a method to take measurements, namely the Student Assessment Sheet (LPS) which consists of three extracurricular aspects, smart books, and discipline. LPS assessment is used to report student progress once a month. Microsoft excel tool used in performing LPS services. The problems that occur in the LPS production process are the data input and the vulnerability that causes the resulting data to be inefficient and not well organized, so a system is built to help the LPS management process with the name Student Assessment Sheet Information System. This system was developed on a website platform so that it can be more clearly structured and visualized. The development method used is the waterfall model. Student order information systems have been tested with white box testing and black box testing on functional requirements and compatibility testing on non-functional requirements. The results given in white box testing are three samples of unit testing and three samples of integration testing, while the results of black box testing are validation testing with valid results in all scenarios. The compatibility tester gives the results that the system can run on various browsers.